Struktur dan ruang dalam arsitektur masjid tradisional nusantara: Studi perbandingan antara daerah - Sulistyana, Anisya Noor (Maliki Interdisciplinary Journal, 2025)
This research discusses the uniqueness of traditional mosque architecture in the archipelago that reflects the fusion of Islamic values and local culture. Using the literature study method, this research highlights the design elements, materials, and spatial functions of mosques in various regions, such as Sunan Giri Mosque in Gresik, Gedhé Mataram Mosque in Kotagede, and Sultan Suriansyah Mosque in South Kalimantan. The method used in this research is a literature study with the main sources used are articles from relevant scientific journals. The results show that each mosque has distinctive characteristics, such as the joglo structure of Sunan Giri Mosque, the use of teak wood at Gedhé Mataram Mosque, and the three-pitched roof at Sultan Suriansyah Mosque which symbolizes the tree of life. The spaces within the mosque are functionally designed for worship and social activities, reflecting local adaptations to Islamic architectural principles. The influence of the kingdoms in each region can be seen in the structural elements, giving a distinctive touch to the local culture. This study emphasizes the importance of preserving traditional mosque architecture as a cultural identity. The study results are expected to be a reference in designing mosques that retain local wisdom while adapting to the times.